Industrial impacts and Indigenous representation: Some fallacies in the Sámi quest for autonomy - Bjørklund, Ivar (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
AbstractWhile Indigenous communities in all circumpolar regions today face increasing pressure from mining companies, their influence in decision-making processes varies substantially. In Norway, the pasturelands of the reindeer-herding Sámi have huge mineral potential and new mining projects are in development. Such projects imply a domino effect, since they tend to generate infrastructures like roads, power lines, and so on. Norway enjoys a high profile as a country strongly committed to Indigenous rights; the Sámi also have their own parliamentary system. Yet to date the Sámi Parliament has been unable to halt these encroachments, a situation in part due to its composition. Because of the electoral rules and the general political position of the reindeer-herding Sámi in Norway, most of the Sámi members of parliament represent interests that run partially counter to the activities of the herders. While Indigenous political participation is territorially defined in Canada and Greenland, this is not the case in Norway.